Molecular interfacial phenomena of polymers and biopolymers - Chen, P. (Pu), 1963- (Woodhead Publishing series in biomaterials., 2005)
This book combines three fundamental areas of interest to the science and engineering community, these being material science, nanotechnology and molecular engineering. Although there have been various results published in this field, there has yet to be a fully comprehensive review. This book covers key research on molecular mechanisms and thermodynamic behaviour of (bio)polymer surfaces and interfaces, from theoretical and experimental perspectives.